2020
DOI: 10.1177/1948550619893968
|View full text |Cite
|
Sign up to set email alerts
|

Empathic and Numerate Giving: The Joint Effects of Victim Images and Charity Evaluations

Abstract: Helping behaviors are often driven by emotional reactions to the suffering of particular individuals, but these behaviors do not seem to be upregulated when many people need help. In this article, we consider if these reactions are also “innumerate” to information about how charities spend their money. Across six experiments, we examined how images of identified victims interact with information about charity efficiency (money toward program) and effectiveness (program outcome). We further examined if the imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Unlike in the previous study, we didn't find significant effects on the amount of money donated, which might stem from the fact that this time we asked participants for real donations not just declarations. It is in line with the results of other studies investigating actual helping behaviors (vs. declarations), showing that the decision whether to donate differs from the decision on how much to donate (Parsons 2007;Karlan and Wood 2017;Bergh and Reinstein 2020).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Unlike in the previous study, we didn't find significant effects on the amount of money donated, which might stem from the fact that this time we asked participants for real donations not just declarations. It is in line with the results of other studies investigating actual helping behaviors (vs. declarations), showing that the decision whether to donate differs from the decision on how much to donate (Parsons 2007;Karlan and Wood 2017;Bergh and Reinstein 2020).…”
Section: Resultssupporting
confidence: 90%
“…It is worth noting that in Study 2, although we found the expected effects on decision whether to donate , we didn’t find them on decision how much to donate . As mentioned above, it is consistent with other studies on actual donations, which demonstrated that the decision to donate differs from the decision on amount of the donation (Parsons 2007 ; Karlan and Wood 2017 ; Bergh and Reinstein 2020 ). Also, Dickert et al ( 2011 ) suggest that donation decisions should be regarded as two-stage process, in which the initial decision to donate (stage 1) is separated from the donation amounts (stage 2).…”
Section: Discussionsupporting
confidence: 90%
“…The evidence for the effectiveness of effectiveness information is mixed. Some studies have found no effect [74,75], while some of our own studies have found a large effect, increasing the proportion of effective donors from zero to 17% or even higher [21,76]. Other studies point to heterogeneity among donors, with minimal effects overall but larger effects for donors who are more altruistically motivated [77] and more educated, especially when encouraged to think more deliberately [78].…”
Section: Strategies To Increase Effective Givingmentioning
confidence: 86%
“…Other studies point to heterogeneity among donors, with minimal effects overall but larger effects for donors who are more altruistically motivated [77] and more educated, especially when encouraged to think more deliberately [78]. Providing more tangible details about a charity's intervention strategies may also make giving more effective [75,79]. All studies to date use limited amounts of effectiveness information, but some donors, including donors willing to give large amounts, may be influenced by more extensive information.…”
Section: Strategies To Increase Effective Givingmentioning
confidence: 99%
“…However, a wealth of psychological evidence suggests that affective processes more strongly influence helping decisions than cognitive processes and rational considerations (see e.g., Farley & Stasson, 2003; Small, 2011). For example, decisions to help are driven more by information that trigger emotional responses, such as images depicting suffering, than rational considerations about the objective effects and efficiency of a donation (Bergh & Reinstein, 2020). The fact that donation decisions are often not driven by rational considerations is vividly illustrated by results found by Evangelidis and Van den Bergh (2013), who show that the number of fatalities, but not the number of survivors, drive donations to disaster relief appeals.…”
Section: Introductionmentioning
confidence: 99%